Universities and startup ecosystems in the national innovation system: the role of Stanford University in Silicon Valley’s success and its influencing factors - Ca, Tran Ngoc; Ha, Chu Thi Thu (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
Many countries expect to build innovation zones and develop technology enterprises similar to the Silicon Valley of the United States, as a component of the national innovation system, but in fact, the reality is very difficult. Many studies have shown that the central ingredient in Silicon Valley's success is Stanford University. This article focuses on analyzing the factors influencing Stanford University in promoting innovation, developing entrepreneurship and the contribution to the success of Silicon Valley. This will be an evocative lesson for countries, including Vietnam, in building factors of the national and regional innovation systems. Code: 20071301